French connection II [videorecording (DVD)] - Frankenheimer, John, 1930-2002; Rosen, Robert L.; Jacobs, Alexander, 1927-1979; Dillon, Robert; Dillon, Laurie; Hackman, Gene; Rey, Fernando, 1917-1994; Fresson, Bernard, 1931-2002; Nesbitt, Cathleen, 1888-1982; Moore, Robin, 1925-2008 (Twentieth Century Fox Home Entertainment, 2001)
Gene Hackman returns in the role of hard-hitting detective Popeye Doyle who travels to Marseilles in pursuit of the heroin dealers who he hit, but failed to kill in New York.